Sacral chordoma with degenerative spondylolisthesis and upper lumbar disc herniation - Shakti A Goel; Hitesh N Modi; Yatin J Desai; Bhavin Patel (Indian Spine Journal, 2019)
Sacral chordoma is a rare condition requiring multidisciplinary approach for management. Here, we report a 72-year-old male patient who was diagnosed with sacral chordoma with L2–L3 disc herniation and L5–S1 degenerative spondylolisthesis and L1 body fracture. The patient was first managed by discectomy L2–L3 with D12–L3 decompression and fixation. Sacral chordoma excision was done 10 months later. The chordoma was excised by anterior laparoscopic resection and mobilization of tissues from the tumor followed by posterior sacrectomy with L5–S1 decompression and extension of fixation in a single stage. Proline mesh was used to support the colon posteriorly. This was further complicated by proximal junction fracture due to fall which was further managed by proximal extension of the rod-screw construct. The patient became symptom free without any radiotherapy or chemotherapy and is able to walk independently, two years following the primary surgery without recurrence of tumor.